Some Ostracoda Species of the Genera Cytherelloidea, Baidria, Loxoconcha, Buntonia, From Khurmala Formation (Late Paleocene-Early Eocene) in Bekhme Dam Village, Peart Anticline, Kurdistan Region, Northeastern Iraq. - M.Aziz, Nisreen; Shaker, Masarra M. (Sulaimani Journal for Pure and Applied Sciences, 2020)
Five ostracoda species belonging to four genera were described from Khurmala Formation (Late Paleocene-Early Eocene) Peart Anticline, Bekhme Dam Village, Kurdistan region, Northeastern Iraq. These species were recorded for the first time, Cytherelloidea bekhmaensis sp.nov., Bairdia Peartensis sp.nov., Loxoconcha harierensis sp.nov., Buntonia bekhmaensis sp.nov., Buntonia peartensis sp.nov. The identified species show strong affinities to those in India, North Africa and Middle East (Southern New Tethys).
Keywords: Ostracoda; Khurmala Formation; Paleocene-Eocene; Kurdistan Region-Iraq